Fauna and flora of drilling and core data from the Iznik Lake: The Marmara and the Black Sea connection - Meric, Engin; Nazik, Atike; Yumun, Zeki U.; Buyukmeric, Yesim; Avsar, Niyazi; Yildiz, Aysegul; Sagular, Enis K.; Koral, Hayrettin; Gokasan, Erkan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The study deals with on the Quaternary connection of the Iznik Lake between the Gemlik Gulf and the Black Sea located in the Marmara Region. The core and drilling data were evaluated. They were collected at two locations and depths from drilling cores and at the three deepest locations of the lake. A total of 510 samples were examined from the lake-bottom cores. Ostracod, mollusc, nannoplankton, ascidian spicule, and diatom assemblages observed at different levels of the drillings were studied. No foraminiferal data were recorded. Molluscan association such as Dreissena bugensis, D. caspia, Monodacna pontica, Clathrocaspia makarovi, Euxinipyrgula milachevitchi, Euxinipyrgula lincta indicate Neoeuxinian age. Amnicythere olivia, A. stepanaitysae, A. striatocostata, Tyrrhenocythere amnicola and Loxoconcha immodulata of the ostracod assemblage, exhibiting Ponto-Caspian origin, were found. In addition, fossil ascidian spicules comprising various species of Bonetia, Micrascidites, Monniotia, and Rigaudia genera were encountered, probably representing Late Pleistocene to Holocene ages. Campylodiscus echeneis, Cocconeis placentula var. lineata Epithemia turgida var. granulata, Epithemia adnata, Nitzschia commutate and N. vermicularis, from the diatom assemblage are genera and species also found in the Iznik Lake and in the Black Sea. Mollusc and ostracod fauna, the Ponto-Caspian origin indicates that the Iznik Lake was connected with the Black Sea and the Marmara Sea in the recent period. Thus, the Ponto-Caspian assemblages indicate the early Neoeuxinian (Surozhian) brackish water inundated the study area. Geochronological ages determined by the C-14 method from the deposits occurring at 53-54 m above present sea level in the Iznik Lake indicate the periods of connection via Iznik Lake during 33,630 to 32,920 cal BP (SK-1) and BP 27,335 to 27,070 cal BP (SK-2). When the position of the deposits is compared with the previously available Late Pleistocene C-14 data obtained from the molluscs identified in the nearby Gemlik Gulf at -76 m present water depth and also with the early Khazarian (Middle Pleistocene) age data on the molusc fauna at 130-150 m heights of uppermost terraces above present sea level to NW of the lake, we suggest the influence of a neo-tectonic regime for the occurrence of comparable age deposits at different levels in the region. It may be proposed that a vertical displacement in the order of a 100 m occurred since the late Pleistocene in the Iznik Lake area and the lake acquired its present features as a result of the tectonic movements. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.
Keywords: Ostracod; Mollusc; Nannoplankton; Ascidian spicule; Diatome; Iznik Lake; Turkey; NORTH ANATOLIAN FAULT; NW TURKEY; OSTRACOD ASSEMBLAGES; DIATOM ASSEMBLAGES; ACTIVE TECTONICS; LATE PLEISTOCENE; CASPIAN SEA; AEGEAN SEA; EVOLUTION; REGION; Physical Geography; Geology